Citizenship as Privilege and Social Identity: Implications for Psychological Distress. (May 2016) - Gee, Gilbert C.; Morey, Brittany N.; Walsemann, Katrina M.; Ro, Annie; Takeuchi, David T.
Citizenship is both a system of privilege and a source of social identity. This study examines whether there are disparities in psychological distress between citizens and noncitizens, and whether these disparities may be explained by markers of social disadvantage (e.g., poverty, discrimination) or perceptions of success in the United States (i.e., subjective social status). We analyze data from the Asian subsample ( n = 2, 095) of the National Latino and Asian American Study. The data show that noncitizens report greater psychological distress compared with naturalized citizens and native-born citizens after accounting for sociodemographics (e.g., age, gender, Asian subgroup), socioeconomic characteristics (education, employment, income-to-poverty ratio), immigration (e.g., interview language, years in the United States, acculturative stress), health care visits, and everyday discrimination. Preliminary evidence suggests that subjective social status may explain some of the disparities between naturalized citizen and noncitizen Asian Americans.